2023
DOI: 10.3389/fgene.2023.1206855
|View full text |Cite
|
Sign up to set email alerts
|

Advanced maternal age: copy number variations and pregnancy outcomes

Abstract: Objective: Adverse pregnancy outcomes are closely related to advanced maternal age (AMA; age at pregnancy ≥35 years). Little research has been reported on aneuploid abnormalities and pathogenic copy number variations (CNVs) affecting pregnancy outcomes in women with AMA. The purpose of this study was to assess CNVs associated with AMA in prenatal diagnosis to determine the characteristics of pathogenic CNVs and assist with genetic counseling of women with AMA.Methods: Among 277 fetuses of women with AMA, 218 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
2
3
0
1
Order By: Relevance
“…The percentage of advanced age (20.64%) was much lower than that of advanced age in the common trisomy (40.62%), confirming that the occurrence of CNVs is independent of maternal age (Avram et al, Frontiers in Genetics frontiersin.org Wu et al, 2021). In addition, we found that some of the abnormalities observed in the fetuses with CNVs were inherited from mothers with intellectual disability, suggesting a genetic link in the production of some fetuses with CNVs (Avram et al, 2021;Cao et al, 2023). In our study, we observed that 83.41% of cases positive for common trisomy exhibited obvious clinical symptoms, whereas only 65.12% of cases positive for CNVs showed such symptoms.…”
Section: Cffdna Fraction Affected Nipt Test Resultssupporting
confidence: 74%
“…The percentage of advanced age (20.64%) was much lower than that of advanced age in the common trisomy (40.62%), confirming that the occurrence of CNVs is independent of maternal age (Avram et al, Frontiers in Genetics frontiersin.org Wu et al, 2021). In addition, we found that some of the abnormalities observed in the fetuses with CNVs were inherited from mothers with intellectual disability, suggesting a genetic link in the production of some fetuses with CNVs (Avram et al, 2021;Cao et al, 2023). In our study, we observed that 83.41% of cases positive for common trisomy exhibited obvious clinical symptoms, whereas only 65.12% of cases positive for CNVs showed such symptoms.…”
Section: Cffdna Fraction Affected Nipt Test Resultssupporting
confidence: 74%
“…The percentage of advanced age (20.64%) was much lower than that of advanced age in the common trisomy (40.62%), confirming that the occurrence of CNVs is independent of maternal age ( Avram et al, 2021 ; Wu et al, 2021 ). In addition, we found that some of the abnormalities observed in the fetuses with CNVs were inherited from mothers with intellectual disability, suggesting a genetic link in the production of some fetuses with CNVs ( Avram et al, 2021 ; Cao et al, 2023 ). In our study, we observed that 83.41% of cases positive for common trisomy exhibited obvious clinical symptoms, whereas only 65.12% of cases positive for CNVs showed such symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…Desse modo, a mulher nasce com seus oócitos definidos que envelhecerão e alguns sofrerão atresia conforme sua idade avança. Cenário esse que predispõe mulheres com idade mais avançada a riscos envolvendo mutações genéticas, pois os oócitos envelhecidos apresentam maiores chances de segregações incorretas entre os cromossomos homólogos durante a meiose I, os quais gerarão células haploides que podem ser responsáveis por anomalias genéticas (BARBOZA et al, 2019;FERREIRA et al, 2022;CAO et al, 2023).…”
Section: Estudounclassified